2010
DOI: 10.1007/s10519-010-9424-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Dyslexia and SLI Risk Variants in Reading- and Language-Impaired Subjects

Abstract: Dyslexia (or reading disability) and specific language impairment (or SLI) are common childhood disorders that show considerable co-morbidity and diagnostic overlaps and have been suggested to share some genetic aetiology. Recently, genetic risk variants have been identified for SLI and dyslexia enabling the direct evaluation of possible shared genetic influences between these disorders. In this study we investigate the role of variants in these genes (namely MRPL19/C20RF3,ROBO1,DCDC2, KIAA0319, DYX1C1, CNTNAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
221
3
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 201 publications
(237 citation statements)
references
References 76 publications
5
221
3
5
Order By: Relevance
“…27 Significant association was identified for quantitative measures of expressive and receptive language ability as well as scores of non-word repetition (which are thought to relate to phonological working memory and therefore language-related processing ability) with a cluster of SNPs within introns 13-14 ( Figure 1a). 20,24 Non-word repetition was similarly associated with one of these intron 13 variants (rs2710102) in a cohort of dyslexia probands. 25 Strong evidence for a connection between CNTNAP2 and ASD has also emerged.…”
Section: Cntnap2 and Cognitive Disorders Mutations Of Cntnap2mentioning
confidence: 99%
See 1 more Smart Citation
“…27 Significant association was identified for quantitative measures of expressive and receptive language ability as well as scores of non-word repetition (which are thought to relate to phonological working memory and therefore language-related processing ability) with a cluster of SNPs within introns 13-14 ( Figure 1a). 20,24 Non-word repetition was similarly associated with one of these intron 13 variants (rs2710102) in a cohort of dyslexia probands. 25 Strong evidence for a connection between CNTNAP2 and ASD has also emerged.…”
Section: Cntnap2 and Cognitive Disorders Mutations Of Cntnap2mentioning
confidence: 99%
“…CNTNAP2 variants are associated with complex disorders Genome-wide association studies have also linked CNTNAP2 to complex neurological disorders, including language impairment, autism, dyslexia, schizophrenia, and depression 18,20,[22][23][24][25][26] (Table 2), although causal variants have not yet been identified. Convincing evidence has linked common variants (ie, single nucleotide polymorphisms; SNPs) in the CNTNAP2 region with the most common form of language disorder in children: specific language impairment (SLI).…”
Section: Cntnap2 and Cognitive Disorders Mutations Of Cntnap2mentioning
confidence: 99%
“…Furthermore, several studies failed to replicate the initial association of rs3743205‐ DYX1C1 found by Taipale et al. (2003) (Bellini et al., 2005; Brkanac et al., 2007; Marino et al., 2005, 2007; Newbury et al., 2011; Saviour et al., 2008; Wigg et al., 2004). …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the identified effect sizes of SNP rs2143340‐ KIAA0319 were reported with opposing risk alleles (Francks et al., 2004; Luciano et al., 2007; Newbury et al., 2011). Contradicting effect size directions of risk alleles were also observed in studies investigating intermediate phenotypes of other diseases: Shulman et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation